2020
DOI: 10.3389/fneur.2020.598851
|View full text |Cite
|
Sign up to set email alerts
|

Increased Anxiety-Like Behavior in the Acute Phase of a Preclinical Model of Periodontal Disease

Abstract: Periodontal disease (PD) is an infectious-inflammatory oral disease that is highly prevalent among adolescence and adulthood and can lead to chronic orofacial pain and be associated with anxiety, stress and depression. This study aimed to identify anxiety-like behaviors in the ligature-induced murine preclinical model of PD in different phases of the disease (i.e., acute vs. chronic). Also, we investigated orofacial mechanical allodynia thresholds and superficial cortical plasticity along the orofacial motor c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Recently, anxiety-like behaviors [assessed using the elevated plusmaze (EPM)] have been reported in Wistar rats submitted to a ligature-induced pre-clinical model of periodontitis in the acute phase (14 days), but not in the chronic phase (28 days) of the disease (82), stressing the importance of timing in this type of longitudinal study to assess anxiety-like defensive behavioral responses, and other behaviors relevant to psychiatric disorders, in an animal model of periodontitis.…”
Section: Findings In Rodentsmentioning
confidence: 99%
“…Recently, anxiety-like behaviors [assessed using the elevated plusmaze (EPM)] have been reported in Wistar rats submitted to a ligature-induced pre-clinical model of periodontitis in the acute phase (14 days), but not in the chronic phase (28 days) of the disease (82), stressing the importance of timing in this type of longitudinal study to assess anxiety-like defensive behavioral responses, and other behaviors relevant to psychiatric disorders, in an animal model of periodontitis.…”
Section: Findings In Rodentsmentioning
confidence: 99%
“…Diabetes coupled with CP increases cardiorenal mortality risk [ 5 ]. The CP patients demonstrated significant endothelial dysfunction [ 56 ], and epidemiological studies revealed a close association between periodontitis and cardiovascular diseases [ 7 ], liver diseases [ 8 ], rheumatoid arthritis [ 57 ], alopecia areata [ 10 ], anxiety-like behaviors [ 11 ], respiratory diseases [ 12 ], and neuropathy in diabetic patients [ 58 ]. Our study provides information regarding molecular signatures, gene expression patterns, protein properties, codon usage, codon bias, information regarding codons influencing codon usage to various extents, and dinucleotide pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic periodontitis (CP) negatively influences glycemic control, and diabetes coupled with CP enhances the risk of cardiorenal mortality [ 5 ]. The CP patients demonstrate significant endothelial dysfunction [ 6 ], and studies revealed a close association between periodontitis and cardiovascular diseases [ 7 ], liver diseases [ 8 ], rheumatoid arthritis [ 9 ], alopecia areata [ 10 ], anxiety-like behaviors [ 11 ], respiratory diseases [ 12 ], and neuropathy in diabetic patients [ 13 ]. In addition, studies have shown that CP enhances the risk of preeclampsia in pregnant women [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that anxiety can lead to behavioral changes that might worsen treatment outcomes, or, in a worst case scenario, lead to treatment interruption [43][44][45][46]. In a murine model of ligature-induced periodontitis, the presence of anxiety-like behaviors was observed in the acute phase of periodontitis, highlighting a potential role for such a psychological trait or state in the pathological process [47]. Here, the association between STAI scores and periodontal parameters evolution was observed.…”
Section: Discussionmentioning
confidence: 99%